Effects of heat stress on the blood pressure and heart rate variability in young men - ÇOTUK, HASAN BİROL (My University, 2013)
Eighteen healthy military college cadets and university students were studied by means of a head-up-tilting test (HUT) in normal (temperature 22°, relative humidity 35%) and hot environment (42°C, 18%). During HUT the beat-to-beat mean blood pressure (MBP) and heart rate (HR) were continuously recorded with a differential oscillometric device. The MBP and HR variability were calculated in segments of 5 min using Fast Fourier Transform to obtain high frequency (HF, 0.15-0.4 Hz) and low frequency (LF, 0.04-0.15 Hz) components. In addition to that, we also computed the time domain indices rMSSD and pNN50 for HR variability analysis. Our study revealed that in the heat the mean values of HR were significantly higher in the supine as well as the tilted position compared to the situation in normothermia. At the same time, the mean values of MBP in the supine and tilted positions in normal as well as heat stress condition were not significantly different. The absolute values of LF and HF components of HR variability decreased in hyperthermia, while no significant changes in spectral indices of MBP variability and normalised values of HR variability were observed. © 2013 IFMBE.
Keywords: blood pressure variability; continuous noninvasive mean blood pressure; head-up-tilting; heart rate variability; Heat stress